Accidental Degeneracy of the Coulomb Interaction - Aldrovandi, R.; Alcabas, J. A.C.; Ferreira, P. Leal (American Association of Physics Teachers (AAPT), 1967)
A treatment of the bound states for the hydrogen atom is given, based on the Sehrodinger equation in momentum representation. The work runs parallel to Fock's treatment of the integral equation in momentum space. The problem is reduced to an eigenvalue equation for the Laplace-Beltrami operator in a momentum space of constant curvature, from which Balmer formula and the eigenfunctions are easily derived. © 1967, American Association of Physics Teachers. All rights reserved.